Desarrollo de un módulo para la gestión del laboratorio clínico de la Universidad Técnica de Cotopaxi empleando el Framework .net - Molina Calvopiña, Erick Joel (2023)
In the Clinical Laboratory of the Technical University of Cotopaxi, it was identified that the documentation related to the results of the clinical examinations is carried out physically, which generates limitations in the time and availability of delivery to the user, for which a module that allows speeding up this process through the integrated system of institutional management. The module consists of the integration of the requesting doctor, who sends the request to the clinical laboratory, in this way the person in charge of the laboratory will take the samples from the user and will be able to enter them into the system, with this the user will access the results directly from the integrated system of management. For the development of the application, the XP methodology was obtained, in addition, the comparison of another methodology known as Crystal will be carried out, this in order to know which was the most agile and simple way.